Implementation of the Project-Based Learning (PjBL) Model in Herbal Plant Processing as an Innovation in Ethnoscience-Based Biology Learning - Andi Sitti Marwah; Indrayani Sima Sima Sohilauw; Intan Kaimudin (Indonesian Journal of Science and Education, 2025)
This study aims to analyze the effectiveness of the implementation of the Project-Based Learning (PjBL) model in herbal plant processing as an ethnoscience-based biology learning strategy, determine its impact on students' understanding of biology concepts, and identify cultural values that can be developed through this learning. The study uses a mixed-methods approach with the following stages: (1) literature study and instrument development, (2) development of an ethnoscience-based PjBL module, (3) implementation in the Herbal Botany course at the University of Muhammadiyah Maluku, (4) observation and data collection through questionnaires, learning outcome tests, and interviews, and (5) descriptive quantitative and qualitative data analysis. The research subjects were 15 students of the Biology Education Study Program. The results showed that the implementation of PjBL was considered effective with an average score of effectiveness indicators in the range of 3.72–3.90 (scale 4), covering aspects of learning design, clarity of instructions, active student involvement, the role of lecturers, and increasing learning motivation. The impact on understanding biological concepts was also significant with an average indicator score of 3.65–3.98, particularly on the ability to link theory to practice, understand the structure and function of herbal plants, and produce products based on scientific concepts. Furthermore, the integration of ethnoscience was proven to strengthen local Maluku cultural values, with indicator scores of 3.74–3.98, such as respect for local wisdom, understanding traditional practices, and awareness of preserving culture through science. Thus, the ethnoscience-based PjBL model is effective as an innovative learning strategy that not only improves students' understanding of biology but also fosters an appreciation for local cultural identity